Cultural empathy in midwifery students: Assessment of an education program. (November 2018) - Hogan, Rosemarie; Rossiter, Chris; Catling, Christine
Abstract: Background: The ability of midwives to provide empathic care that is culturally appropriate is critical for women to feel accepted by the midwives who support them. Australia is a culturally diverse society, yet there is evidence of poorer maternity outcomes for some women and infants, related to their cultural background. Objectives: This study's objective was to evaluate the effectiveness of an education program for student midwives. The program was intended to increase the cultural empathy of future midwives, to help ensure greater cultural safety and optimal maternity outcomes across all sections of Australian society. Design: This quantitative study compared pre- and post-intervention measures of students' empathy. Setting: The health faculty of a large urban university in Australia. Participants: Fifty-five students from all three years of an undergraduate midwifery program participated. Methods: The study examined students' scores on the Jefferson Scale of Empathy for health profession students, measured before and immediately after the education program, and again after four weeks. Results: The midwifery students had a high mean baseline score on the empathy scale. Scores increased significantly after the education program. Students with lower pre-test scores recorded significantly greater increases in their empathy levels than those who were more empathic initially. Empathy scores declined one month after the program, but remained higher than baseline levels. Conclusions: Several studies have explored empathy levels amongst current and future health professionals. However, few studies of health professional students have evaluated the impact of specific education interventions addressing cultural empathy. This study found that midwifery students tended to have higher empathy scores than students in other health disciplines. The education workshop further increased participants' scores. Highlights: This study acknowledges cultural diversity amongst childbearing women through enhancing cultural empathy in midwifery students. Participants' empathy scores increased following education about culturally competent midwifery care. Students who were less empathic initially experienced greater increases in empathy scores after the program. Despite some decline over time, empathy levels remained higher than before the education program.